Evaluation of some soil physical properties in different lanscape - Noguera J, Maritza Alejandra; Vélez L., Jorge Alberto (Revista de Ciencias Agrícolas, 2011)
The study was conducted in Trojayaco soils, a rural area in the municipality of El Tambo, Nariño, with an average temperature of 18 ° C at 2200 a.s.l.m, its geographical coordinates are 1 ° 24 ’north latitude and 77 ° 27’ west longitude . We evaluated the apparent density (da), real density (rd), total porosity (pt), hydraulic conductivity (k), penetration resistance (rp) in five treatments: T1 (Pennisetum clandestinum), forest T2, T3 ( Senna pistacifolia -Pennisetum clandestinum), T4 (Eucalyptus glóbulos - Pennisetum clandestinum), T5 (Delastoma integrifolium - Pennisetum clandestinum), furthermore the percentage of dry matter for kikuyo grass was determined. The results showed that the landscape of forest T2, T3 (Senna pistacifolia - Pennisetum clandestinum), T5 (Delastoma integracifolium - Pennisetum clandestinum) and T4 (Eucaliptus globulos - Pennisetum clandestinum) had high total porosity, hydraulic conductivity and lowaverage apparent density and penetration resistance, on the other hand, T1 (Pennisetum clandestinum) showed a decrease in total porosity and hydraulic conductivity, increased bulk density and penetration resistance. T3 and T5 treatments showed better values for dry matter percentage, in change, T4 and T1 treatments showed a significant decreasing this variable